2008
DOI: 10.1016/j.ophtha.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Intraocular Pressure Fluctuations and Risk of Conversion from Ocular Hypertension to Glaucoma

Abstract: Purpose-To investigate whether long-term intraocular pressure (IOP) fluctuations are a risk factor for conversion from ocular hypertension to glaucoma. Design-Observational cohort study.Participants-The study included 252 eyes of 126 patients with ocular hypertension observed untreated as part of the Diagnostic Innovations in Glaucoma Study. At baseline, ocular hypertensive eyes had elevated IOP, normal visual fields (VFs) on standard automated perimetry, and normal optic discs as evaluated by stereophotograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 22 publications
4
108
1
8
Order By: Relevance
“…3 The European Glaucoma Prevention Study (EGPS) suggested a similar effect attributable for each 1-mm Hg-higher IOP (11%), 8 and the Diagnostic Innovations in Glaucoma Study (DIGS) reported that each 1-mm Hg-higher mean follow-up IOP increased the risk of conversion from OHT to glaucoma by 20%. 23 Using trend analysis, Folgar et al 24 recently reported that an average IOP reduction of 40% following glaucoma surgery resulted in a 70% reduction in global rates of VF change and that locations progressing significantly before intervention had their progression either halted or slowed significantly. They also found that for each 1-mm Hg-lower postoperative IOP, the velocity of VF deterioration was slowed by 0.1 dB/year.…”
Section: Discussionmentioning
confidence: 99%
“…3 The European Glaucoma Prevention Study (EGPS) suggested a similar effect attributable for each 1-mm Hg-higher IOP (11%), 8 and the Diagnostic Innovations in Glaucoma Study (DIGS) reported that each 1-mm Hg-higher mean follow-up IOP increased the risk of conversion from OHT to glaucoma by 20%. 23 Using trend analysis, Folgar et al 24 recently reported that an average IOP reduction of 40% following glaucoma surgery resulted in a 70% reduction in global rates of VF change and that locations progressing significantly before intervention had their progression either halted or slowed significantly. They also found that for each 1-mm Hg-lower postoperative IOP, the velocity of VF deterioration was slowed by 0.1 dB/year.…”
Section: Discussionmentioning
confidence: 99%
“…94 In the EGPS, the area under the curve of IOP, a 'time-dependent' evaluation of IOP, taking into account the IOP behaviour for each 6-month period, was associated with the development of OAG yet IOP fluctuation during follow-up was not. 91 Medeiros and colleagues 95 found that longterm IOP fluctuations were not a significant risk factor for glaucoma development in untreated patients with OHT observed over time, but higher mean IOP levels were consistently associated with increased likelihood of developing glaucoma. Similarly, in the Malmö Ocular Hypertension Study, IOP fluctuations were not an independent risk factor for the incidence of glaucomatous visual field loss in patients with OHT, and higher IOP fluctuation was found in eyes with higher IOP levels.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…62 High mean IOP has also been consistently associated with glaucoma progression. 63,64 While peak IOP detection is based on measurements at office visits, the mean IOP requires longitudinal IOP data collection and may be affected by the interval between visits. Establishing a target peak IOP is clinically easier than establishing a target mean IOP in many patients.…”
Section: Iop Peaks and Mean Are Not Adequately Assessedmentioning
confidence: 99%
“…[65][66][67] Other authors considered that IOP fluctuation is not an independent risk factor for glaucoma onset or progression. 63,64,68 This discrepancy may be due to the use of different hypotensive medications, different populations and study designs, as well as the lack of a standard definition and reproducibility of IOP fluctuation. 69,70 The true role of IOP fluctuation, including both short-and long-term variability, has not yet been adequately addressed in clinical trials given the difficulty in performing diurnal curves in all patients on a regular basis.…”
Section: Iop Peaks and Mean Are Not Adequately Assessedmentioning
confidence: 99%